Generalizable representations of pain, cognitive control, and negative emotion in medial frontal cortex - Kragel, P; Kano, M; Van Oudenhove, L; Ly, H; Dupont, P; Rubio, A; Delon-Martin, C; Bonaz, B; Manuck, S; Gianaros, P; Ceko, M; Reynolds Losin, E; et al. (Springer Nature, 2018)
The medial frontal cortex, including anterior midcingulate cortex, has been linked to multiple psychological domains, including cognitive control, pain, and emotion. However, it is unclear whether this region encodes representations of these domains that are generalizable across studies and subdomains. Additionally, if there are generalizable representations, do they reflect a single underlying process shared across domains or multiple domain-specific processes? We decomposed multivariate patterns of functional MRI activity from 270 participants across 18 studies into study-specific, subdomain-specific, and domain-specific components and identified latent multivariate representations that generalized across subdomains but were specific to each domain. Pain representations were localized to anterior midcingulate cortex, negative emotion representations to ventromedial prefrontal cortex, and cognitive control representations to portions of the dorsal midcingulate. These findings provide evidence for medial frontal cortex representations that generalize across studies and subdomains but are specific to distinct psychological domains rather than reducible to a single underlying process.